Musik i migrationslitteratur. Analyse af eksplicitte referencer til musik i Alen Meškovićs romaner - Slouková, Radka (Folia Scandinavica Posnaniensia, 2019)
This article analyses explicit references to music in the novels of the Danish-Bosnian writer Alen Mešković Ukulele-jam (2011) and Enmandstelt (2016). Mešković is a traditional representative of migration literature because he experienced migration himself and reflects his experiences in his work. Music plays a crucial role in both his novels and appears primarily in the form of explicit references to various Yugoslavian and English singers and songs on the text level. These references work in various ways: they emphasize the difference between East and West, characterize the protagonist, illustrate the atmosphere of the situation, enable the reader to identify with the characters and, last but not least, support the authentic tone of the text, which is a typical feature of migration literature.